Real-time Digital Control of a Coupled-Tank Plant with a Cyber-Physical System Node (ELEKTRIKA- Journal of Electrical Engineering, 2020)
A real-time implementation of a digital proportional-integral controller on a Cyber-Physical Systems (CPS) node for a coupled-tank plant to provide a testbed for verification of control algorithm and communication is described. The CPS node embedded computer is based on the ADuC841 8-bit microcontroller and the embedded real-time multitasking software was written in Pascal language.Â  The node is interfaced to the Quanser's coupled-tank plant via the on-chip 12-bit analog-to-digital and digital-to-analog converters, and a RS-485 communication network connects it to other nodes to form a CPS. Experimental results on the closed-loop control performances of the digital proportional-integral controller with three different tuning sets on the coupled-tank plant, verified the functionality of the digital control algorithm.
Keywords: Real-time digital control; Cyber-physical systems; Proportional-integral control; Coupled-tank plant